"Análisis a flexión en vigas de concreto armado, compuestas de Hormigón Modificado con fiblillas recicladas de neumático, y su influencia en la cuatía de acero en un Hormigón Estructural de f¨c= 210 kg/cm2". - Rodríguez Almache, Aracelly Estefanía (2016)
The research carried out in this document corresponds to the civil engineering degree project at the National University of Chimborazo, focused on the flexural behavior analysis of a modified concrete with fibers extracted from the destruction of tires in disuse, the specific purpose is to know the impact that the contribution of these fibers have on the amount of steel to design simple reinforced beams. The project is basically divided into three stages and a preliminary stage. The preliminary stage corresponds to the search for suppliers of the required fiber, in which finally the raw material of the company Facerquim S.A was used, this company is dedicated to the manufacturing of floors with recycled fibers fromused tires; meanwhile, in the laboratory, the mechanical properties of aggregates from Hnos. Castro- Cerro Negro were determined and the design of the concrete mix that reaches the resistance of f'c = 210 kg/cm2. In the First Stage, test tubes of conventional and modified concrete were prepared for testing compressive and flexural at 2, 3, 4, 5 and 6% by weight of fine aggregate replaced by recycled rubber tire fibers, in order to reach optimal fiber addition rate that works with concrete so that it reaches the specified resistance and compression presenting flexural characteristics for helping to achieve a better resistance to breakage of the beams. The selected percentage was 4%. The Second Stage corresponds to the production of beams for bending tests, this time with 4% of coarse aggregate replaced by fiber. The concrete-steel adhesion tests were also performed by a method designed by the director and thesis developers. Stage Three, finally corresponds to the production of just 10x10x60 cm armed beams and 6 mm rebar in diameter, the design was developed with the properties of modified concrete that were determined in the previous stages. At this stage the incidence of the rubber fibers in the concrete were verified, by testing flexion on beams, resulting in a higher resistance of top flexural loads in relation to conventional concrete.